O uso das TICs nas resoluções matemáticas: uma análise acerca das dificuldades na utilização do App ábaco digital na resolução das operações matemáticas - CRUZ, Adriany Ferreira (Instituto Federal do Amapá, 2021)
The present research consisted of an analysis about the difficulties of the 5th grade students of the Murilo Braga State School, in the use of APP Abacus digital in the resolution of mathematical operations. The objective was to investigate the students 'qualitative and quantitative reaction to the use of Information and Communication Technologies (ICTs) as didactic resources, to observe the students' ability to use digital Abacus, as well as to understand the ability to use technological resources in the educational process. It was based on a bibliographical and field research, with qualitative and quantitative methods with descriptive analytical approach. The technique of data collection was carried out from a structured questionnaire, where we sought to understand sociocultural characteristics of the researched subject; an activity with basic operations of mathematics, using as technological resource the Digital abacus for the demonstration of the results, besides an observation sheet used by the researchers. It was found that the difficulties presented were due to the participants of the research do not have a cell phone, do not like Mathematics, do not know what is unity, dozens and hundreds, as well as not having intimacy with the Digital Abacus application.